Physically crosslinked poly(vinyl alcohol)–carrageenan composite hydrogels: pore structure stability and cell adhesive ability. Issue 95 (15th October 2015) - Zhang, Yabin; Ye, Lei; Cui, Man; Yang, Boguang; Li, Junjie; Sun, Hong; Yao, Fanglian
<x xml:space="preserve">Abstract</x> Poly(vinyl alcohol) (PVA)–carrageenan (CAR) composite hydrogels can reduce pore collapse during lyophilization and enhance cell adhesion in comparison to pure PVA hydrogels.